(untitled) (Research, Society and Development, 2025)
This study aimed to evaluate the impact of grayscale inversion, also known as the negative filter, on the physical quality of chest radiographs. This technique emerges as a promising alternative for enhancing anatomical details in low-contrast regions, thereby contributing to the optimization of diagnostic interpretation. The investigation was conducted through a comparative analysis of quantitative image quality (IQ) descriptors: Signal-to-Noise Ratio (SNR), Contrast-to-Noise Ratio (CNR), and Radiographic Contrast (RC). The results showed an increase of 15.7% in SNR and 9.9% in CNR, indicating, respectively, greater definition of anatomical structures and improved ability to differentiate tissues with similar densities—an essential characteristic for highlighting subtle details in pulmonary parenchyma. Conversely, a 5.71% reduction in RC was observed, a predictable effect resulting from tonal inversion, which smooths the overall contrast inherent to the positive scale. Therefore, it is concluded that the application of the negative filter preserves diagnostic image quality while enhancing the perception of subtle anatomical structures in chest radiographs.